ESTETIKA DAN KRITIK SOSIAL DALAM KARYA LIPUTAN “HEGEMONI INDUSTRI KOPI” DI CHANNEL YOUTUBE SUAR NUSANTARA - Cory Amelia Lorenza (Institut Seni Budaya Indonesia Bandung, 2021)
The rise of coffee shops in the city of Bandung has made the coffee industry sector grow rapidly. This industry generates a lot of profits from upstream “farmers” to downstream “entrepreneurs” of coffee shops. However, at the same time, this industry creates quite a big problem, especially in the presentation media and the waste generated from the industry. Suar Nusantara managed to package it in a work of coverage that combines elements of art in it. This study uses a qualitative method with semiotic analysis of Roland Barthes. From the results of the research, it is known that the work covering the